Rancang Bangun Sistem Informasi Administrasi Tamu Menggunakan RUP (Rational Unified Process) Pada Losmen Wedy Jaya - Melano, Reynaldi; Prasetyaningrum, Eka (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Guest data processing at Wedy Jaya Inn is not in accordance with today's technological developments. In processing guest data, the receptionist still uses a notebook to record guest reservation data and to perform check-in and check-out transactions for inn guests. This research was conducted using the RUP (Rational Unified Process) model research method. Data collection techniques were carried out by means of observation and literature study. The problem is that the guest administration process and data processing are still manual, starting from guest data to storing other data related to transactions to making reports. So because it is possible during the process there is an error in recording, less accurate reports are made and delays in the required search. Then there is no online room availability checking system which makes guests have to come directly to the Wedy Jaya inn to check if there are still rooms available and this can take a lot of time. The solution is to create a website-based system for inn guest data processing that will make it easier for receptionists to collect reservation data, input check-in and check-out of inn guests. Designing a database that will accommodate all data related to reservations, check-in and check-out of inn guests. A website-based system for inn guest data processing can simplify and speed up the tasks of the receptionist in data collection of reservations, check-in and check-out of inn guests as well as in making reports needed by inn owners and employees as well as providing a system that can be used to check room availability using the RUP method. Rational Unified Process)